ANALISIS KESULITAN PEMECAHAN MASALAH MATEMATIKA MATERI PERKALIAN DAN PEMBAGIAN KELAS III SDN PANDEAN LAMPER 02 - Sustya Dinata, Nia; Sulianto, Joko; Patonah, Siti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the large number of students who still have difficulty in solving mathematical problems of multiplication and division materials, students also have difficulty understanding the material and solving mathematical problem solving problems. With that, influencing factors in solving math problems because students experience difficulties in reading and arithmetic. This study aims to describe the difficulties experienced by students in solving mathematical problems of multiplication and division materials and identify the factors that cause difficulties in solving mathematical problems of multiplication and division materials in grade III SDN Pandean Lamper 02. This study uses a descriptive qualitative approach with 23 students in grade III of SDN Pandean Lamper 02. Data collection techniques are carried out through observation, written tests, interviews and documentation. The results of this study show that the difficulty of solving mathematical problems in doing multiplication and division problems as a whole is above 70%. Questions number 5 and 8 became the most mastered instruments with a success rate of 100%, followed by question number 6 (96%). On the other hand, questions 10 and 4 were the most difficult instruments with an error rate of 39% and 30%, respectively. It is found that with the level of belief, namely understanding concepts, misconceptions and misconceptions, difficulties in solving problems, students are not able to understand the problem well so that students have difficulty in applying the right formulas or theories to solve problems